Mood Variability Among Early Adolescents in Times of Social Constraints: A Daily Diary Study During the COVID-19 Pandemic - Asscheman, J. Susanne; Zanolie, Kiki; Bexkens, Anika; Bos, Marieke G. N. (Frontiers in Psychology, 2021)
The COVID-19 pandemic and associated governmental regulations have drastically changed the daily social lives of children, adolescents and adults. Changes in the social context may particularly affect children who are in the transition to adolescents (henceforth referred to as early adolescents) as adolescence is a crucial period for peer interactions and development of independence and autonomy. Yet, the impact of the pandemic and associated governmental regulations on early adolescents’ emotional well-being has yet to be clarified. In the current study, we explored daily fluctuations in mood in 54 early adolescents (Mage = 11.07) during the first few months of the COVID-19 pandemic. Moreover, the role of parents and peers on adolescents’ mood variability was investigated. Adolescents rated their mood (i.e., happiness, anger, sadness, anxiety) and peer interactions once a day during four separate weeks across different weeks of containment measures in the Netherlands. Moreover, adolescents reported on their experienced attachment to parents and peers and internalizing problems during baseline and the final measurement, respectively. Results showed relatively stable levels of mood during the first few months of the COVID-19 pandemic. However, individual differences in mood variability during the first assessment week were negatively associated with the experienced level of attachment to both parents and peers. Moreover, heightened levels of mood variability did not mediate the link between attachment and internalizing problems. Lastly, the quality of offline contact, but not online contact, was negatively related to adolescents’ mood variability. Overall, this study suggests that mental well-being of early adolescents may not necessarily be affected by the COVID-19 crisis, and that social connectedness to parents or peers may facilitate resilience to distress and daily mood fluctuation in early adolescents.